On closeness of the sum of n subspaces of a Hilbert space - Feshchenko, I. S. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We give necessary and sufficient conditions for the sum of subspaces $H_1,..., H_n,, \quad n ≥ 2,$ of a Hilbert space $H$ to be a subspace and present various properties of $n$-tuples of subspaces with closed sum.